Wuling powder ameliorates diarrhea-predominant irritable bowel syndrome in mice by modulating gut mucosal microbiota and alleviating intestinal inflammation - Qianghong Tian; Donglin Yu; Junxi Shen; Leyao Fang; Ying Cai (Frontiers in Cellular and Infection Microbiology)
ObjectivesWuling powder has been widely used for the clinical treatment of IBS-D, but the microecological mechanism has not been found. This study aimed to investigate the regulatory effect of Wuling powder on intestinal mucosal microbiota in mice with diarrhea predominant-irritable bowel syndrome (IBS-D) by 16S rRNA high-throughput sequencing.MethodsMice were randomly divided into normal control group (Mc), model control group (Mm), and treatment group (Mt). The IBS-D model was induced via Folium sennae gavage and acute restraint stress, and treatment was conducted with Wuling powder. Serum levels of tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), and milk fat globule EGF factor 8 (MFGE8) were quantified via enzyme-linked immunosorbent assay (ELISA). Intestinal mucosal DNA was extracted for 16S rRNA gene high-throughput sequencing to analyze microbial community alterations. We analyzed the characteristics of the intestinal mucosal microbiota and explored the potential link between the intestinal mucosal microbiota and the inflammatory response.ResultsCompared with the Mc group, the Mm group presented markedly elevated serum TNF-α and IL-6 concentrations (p<0.001; p<0.001) and significantly decreased MFGE8 levels (p<0.01). In contrast, the Mt group presented significant reductions in TNF-α and IL-6 (p<0.05; p<0.05) and a pronounced increase in MFGE8 (p<0.01) relative to those in the Mm group. After treatment with Wuling powder, the abundance and diversity of the intestinal mucosal microbiota were restored. The characteristic genus Sporosarcina was significantly positively correlated with MFGE8, and Paludibaculum was significantly negatively correlated with TNF-α and IL-6.ConclusionWuling powder may inhibit the occurrence of an inflammatory response by reducing the TNF-α and IL-6 levels and increasing the MFGE8 level and may achieve the effect of treating IBS-D by regulating the composition, structure, and function of the intestinal mucosal microbiota, which provides new ideas for the clinical prevention and treatment of IBS-D via Wuling powder.